THU0110 DISEASE ACTIVITY AND PATIENT-REPORTED OUTCOMES IN PATIENTS WITH RA WITH SJÖGREN'S SYNDROME ENROLLED IN A LARGE OBSERVATIONAL US REGISTRY. (June 2019) - Harrold, Leslie R; Shan, Ying; Rebello, Sabrina; Kramer, Neil; Connolly, Sean; Alemao, Evo; Kelly, Sheila; Kremer, Joel; Rosenstein, Elliot D
Abstract : Background: Sjögren's syndrome (SS) is known to occur secondary to RA diagnosis, but its impact on RA outcomes is poorly understood. In the US-based Corrona registry, SS has a prevalence rate of 0.30 in patients (pts) with RA. 1 Objectives: To compare disease activity and patient-reported outcomes (PROs) in pts with and without SS, in a national sample of pts with RA. Methods: We identified adult pts with rheumatologist-diagnosed RA from a large observational US registry (Corrona RA), with at least one visit with known SS status between 22 Apr 2010 and 31 Jul 2018 and a visit 12 (±3) months after index date. SS status was captured using physician forms at enrollment and follow-up visits. The index date was the date of first capture of SS diagnosis, or first visit in which SS status was recorded for pts without a diagnosis of SS (non-SS pts). Both those with and without SS were required to have initiated a targeted synthetic (ts) or biologic (b)DMARD. Non-SS pts had to be enrolled for ≥12 months. Pts were frequency matched 1:1 based on RA duration prior to 1:1 propensity score matching (PSM) based on variables associated with treatment response. Outcomes 12 months after index visit were compared in pts with and without SS. Primary outcome was mean change in CDAI score from index visit to Month 12; secondary outcome was mean change in PROs (pain, fatigue, pt global assessment and morning stiffness). Results: After PSM, baseline characteristics in 283 pairs of pts with and without SS were well balanced (Table 1 ). Mean change in CDAI score was numerically lower in SS than non-SS pts (8.8 vs 9.3; Table 2 ), but this did not reach statistical significance. Improvements in pain, fatigue and stiffness were 2–2.5-fold greater for non-SS than SS pts (Table 2 ). Conclusion: Among those initiating b/tsDMARD treatment, improvements in RA-related PROs were lower in pts with RA with SS than non-SS pts. Physicians may want to consider SS status secondary to RA when managing pts with RA and specifically explore whether additional intervention is needed to improve the pt experience for pts with RA. References: [1] Harrold LR, et al. Arthritis Rheumatol. 2018;70(suppl 10): abstract 541. Acknowledgement: This study was sponsored by Corrona, LLC. Corrona is supported through contracted subscriptions with multiple pharmaceutical companies. The abstract was a collaborative effort between Corrona and Bristol-Myers Squibb (BMS) with financial support provided by BMS. Professional medical writing: Lola Parfitt, MRes, Caudex; funding: BMS Disclosure of Interests: Leslie R Harrold Shareholder of: Corrona LLC, Grant/research support from: Grant funding: Pfizer, Consultant for: AbbVie, Bristol-Myers Squibb, Genentech, Employee of: Corrona LLC, Ying Shan Employee of: Corrona LLC, Sabrina Rebello Employee of: Corrona, LLC, Neil Kramer Shareholder of: Johnson & Johnson, Pfizer, Regeneron, AbbVie, Amgen, Sean Connolly Shareholder of: Bristol-Myers Squibb, Employee of: Bristol-Myers Squibb, Evo Alemao Shareholder of: Bristol-Myers Squibb, Employee of: Bristol-Myers Squibb, Sheila Kelly Shareholder of: Bristol-Myers Squibb, Employee of: Bristol-Myers Squibb, Joel Kremer Grant/research support from: AbbVie, Genentech, Lilly, Novartis, Pfizer, Consultant for: AbbVie, Amgen, BMS, Genentech, Lilly, Regeneron, Sanofi, Pfizer, Elliot D Rosenstein Grant/research support from: AbbVie, Novartis, Consultant for: Amgen, Bristol-Myers Squibb, Boehringer Ingelheim, Speakers bureau: Amgen, Bristol-Myers Squibb